2021
DOI: 10.3390/genes12101480
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Perinatal and Early Life Outcomes following 15q11.2 CNV Diagnosis

Abstract: The copy number variation (CNV) of 15q11.2, an emerging and common condition observed during prenatal counseling, is encompassed by four highly conserved and non-imprinted genes—TUBGCP5, CYFIP1, NIPA1, and NIPA2—which are reportedly related to developmental delays or general behavioral problems. We retrospectively analyzed 1337 samples from genetic amniocentesis for fetal CNV using microarray-based comparative genomic hybridization analysis between January 2014 and December 2019. 15q11.2 CNV showed a prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The deletion carriers are reported to be more symptomatic and have higher neonatal intensive care unit (ICU) transfer, while our study has not shown such tendency. Interestingly, Chu et al have mentioned that the prevalence of congenital heart disease was also higher in the deletion group, and most of our ultrasound abnormalities in the deletion group are cardiovascular ( 31 ). The other two case reports were cases with 15q11.2 BP1–BP2 duplication.…”
Section: Discussionmentioning
confidence: 67%
“…The deletion carriers are reported to be more symptomatic and have higher neonatal intensive care unit (ICU) transfer, while our study has not shown such tendency. Interestingly, Chu et al have mentioned that the prevalence of congenital heart disease was also higher in the deletion group, and most of our ultrasound abnormalities in the deletion group are cardiovascular ( 31 ). The other two case reports were cases with 15q11.2 BP1–BP2 duplication.…”
Section: Discussionmentioning
confidence: 67%